Selected Decisions and Selected Documents of the International Monetary Fund, 34th Issue. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2010)
Selected Decisions and Selected Documents of the International Monetary Fund includes decisions, interpretations, and resolutions of the Executive Board and Board of Governers of the IMF, as well as selected documents to which frequent reference is made in the current activities of the Fund. In addition, it includes certain documents pertaining to the relations between the Fund and other international organizations.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet